IMPLEMENTATION OF THE STUDENT-LED CONFERENCE METHOD TO DEVELOP CHILDREN'S SELF-RELIANCE - Dwiyani Hermawati; Ani Rohaeni; Sri Nurhayati; Ansori Ansori (IKIP Siliwangi Bandung, 2021)
This research aims to get an overview of the Student-Led Conference (SLC) method in developing the character of children's self-reliance in The Pelopor Nature School of Rancaekek Subdistrict, Bandung Regency. The research uses qualitative research. The method used to analyze the data is a qualitative descriptive approach. The subjects of this study were group B children, consisting of 15 children, parents of 5 students and two teachers. Research involves gathering information by observation, interviewing, and documentation. The data comes from formal documents such as observation sheets, and informal observations. A data analysis process using Miles & Huberman's interactive data collection, data visualization, data reduction, and drawing of a conclusion. The study showed that students who have been taught by the SLC method gain a certain amount of self-reliance. This is indicated by the child's confidence, courage, willingness to take risks and pride in doing their work. Keywords: Early Childhood, Student-Led Conference Method, Self-reliance